Effectiveness of Organic Fertilizer on Growth and Production of Cabbage Plant (Brassica oleraceae) - Sugiono, Sugiono; Krismawati, Amik (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2020)
Research on the effectiveness test of organic fertilizer contains 18% C - Organic growth and production of cabbage was conducted from October 2017 to April 2018. This research aims to examine the effectiveness of organic fertilizer on the growth and yield of cabbage plants. The method of this research used a randomized block design, which consisted of 9 treatments and 3 replications. The location of the research was on dry soil at Dusun Jeding, Junrejo Village, Batu (1000 m asl). Result of soil analysis before the research with pH neutral, low N, higher P2O5, low CEC (Cation Exchange Capacity), and low C-organic, as well as clay loam. The results of the research showed that the application of organic fertilizer significantly affects on plant height, numbers of the leaf, width of canopy, diameter of the crop, and weight of yield. The dose of 800 kg/ha produces a net weight of 24.9 t/ha by the highest value of RAE 408.35. However, the application of Petroganik fertilizer 500kg/ha, it produces a net weight of 18.10 t/ha by RAE value 256.28. Application of the recommended fertilizers (Urea 200, ZA 250, SP-36 250, and KCl 200kg/ha) and organic fertilizer 500-800 kg/ha could increase the growth and production of cabbage by B/C Ratio 2.61. It can be concluded that organic fertilizer â€œBukit Daunâ€ was effective in increasing the growth and yield of cabbage